Fratture dell’omero distale: trattamento con protesi di gomito - Ritali, A.; Guerra, E.; Ricciarelli, M.; Zaccaro, R.; Rotini, R. (Lo Scalpello - Journal, 2019)
ELBOW REPLACEMENT FOR DISTAL HUMERAL FRACTURESThe treatment of distal humeral fractures could be challenging, especially in the older population. Although somefractures of the distal humerus in the elderly can be managed non-operatively, generally they results in poor outcome,secondary stiffness or nonunion. In young people and in patients with good bone quality, open reduction and stableinternal fixation are mandatory, but in patients over 65 y-o, elbow prosthesis could be a good option for treatment. Ifthe patient presents a complex pattern including fracture, osteoporosis, or joint damage from rheumatoid arthritis,total elbow replacement needs to be considered. By contrast, in case of more active patients distal humeralhemiarthroplasty is the ideal choice, being less invasive, with many advantages such as lower patient morbidity, lessconcerns regarding polyethylene wear, and bone stock preservation for future reconstructive procedures. In this studywe reviewed 49 patients, with a mean age of 78. 4 year, who had been treated in our Unit between 2001–2016 fordistal humeral fractures. All patients underwent joint replacement (either total elbow arthroplasty or distal humeralhemiartoplasty). The aim of this study was to assess the outcomes in patients treated with elbow replacement atmedium-term follow-up and, consequently, to define an algorithm for the treatment of distal humeral fractures inelderly.